Venetoclax-rituximab with or without bendamustine vs bendamustine-rituximab in relapsed/refractory follicular lymphoma - Zinzani, Pier Luigi (Blood, 2020)
This open-label phase 2 study (CONTRALTO) assessed the safety and efficacy of BCL-2 inhibitor venetoclax (VEN) plus rituximab (R), and VEN plus bendamustine (B) and R, vs B + R (BR) alone in relapsed/refractory (R/R) follicular lymphoma. Patients in the chemotherapy-free arm (arm A: VEN + R) received VEN 800 mg/d plus R 375 mg/m(2) on days 1, 8, 15, and 22 of cycle 1 and day 1 of cycles 4, 6, 8, 10, and 12. After a safety run-in with VEN 600 mg, patients in the chemotherapy-containing cohort were randomized to either VEN + BR (arm B; VEN 800 mg/d for 1 year + 6 cycles of BR [B 90 mg/m(2) on days 1 and 2 and R 375 mg/m(2) on day 1]) or 6 cycles of BR (arm C). Overall, 163 patients were analyzed (9 in the safety run-in and 52, 51, and 51 in arms A, B, and C, respectively). Complete metabolic/complete response rates were 17% (arm A), 75% (arm B), and 69% (arm C). Of patients in arm B, only 61% received ≥90% of the planned B dose vs 96% of patients in arm C. More frequent hematologic toxicity resulted in more reduced dosing/treatment discontinuation in arm B vs arm C. Rates of grade 3/4 adverse events were 51.9%, 93.9%, and 60.0% in arms A, B, and C, respectively. VEN + BR led to increased toxicity and lower dose intensity of BR than in arm C, but efficacy was similar. Optimizing dose and schedule to maintain BR dose intensity may improve efficacy and tolerability of VEN + BR, while VEN + R data warrant further study. This study was registered at www.clinical trials.gov as #NCT02187861.